Detection of virulence factor encoding genes on Escherichia coli isolated from broiler chicken in Blitar District, Indonesia - MUSTOFA HELMI EFFENDI; HAYYUN DURROTUL FARIDAH; FRESHINDY MARISSA WIBISONO; FRESHINTA JELLIA WIBISONO; NABILATUN NISA; FATIMAH FATIMAH; EMMANUEL NNABUIKE UGBO (Society for Indonesian Biodiversity, 2022)
Abstract. Efendi MH, Faridah HD, Wibisono FM, Wibisono FJ, Nisa N, Fatimah F, Ugbo EN. 2022. Detection of virulence factor encoding genes on Escherichia coli isolated from broiler chicken in Blitar District, Indonesia. Biodiversitas 23: 3437-3442. Broiler chicken is a source of protein that is widely consumed by the public. However, broiler chicken production sometimes decreases due to infectious diseases such as colibacillosis caused by pathogenic Escherichia coli possessing virulence genes. Virulence factors function to facilitate colonization and invasion of host cells to cause disease. The presence of these virulence factors is encoded by various genes such asthe increased serum survival gene and P fimbriae gene which plays a role in surface adhesion. The present study aims to detect the presence of virulence genes from extended-spectrum beta-lactamase (ESBL) producing E.coli isolated from broiler chickens in the Blitar District. A total of 110 cloacal swabs collected by systematic random sampling from broiler poultry farms in four different sub-districts were screened for ESBL-producing E. coli and virulence genes by phenotypic and molecular methods, respectively. Out of 110 E.coli recovered, 95 (86.4%) were observed to show a high level of resistance to the tested antibiotics, and 34 (35.7%) were ESBL-producers. Among ESBL producing E. coli isolates, 22 (73.5%) and 1 (2.9%) were found to have the iss and papC gene virulence factors, respectively using the polymerase chain reaction (PCR) method. The results of this study indicate that virulence genes can be found in E. coli from poultry farms. The iss gene is the most predominant virulence gene. The reportof these virulence factors in E. coli isolated from broiler could impose a serious potential public health problem.